Similarities and Differences between U.S. and German Regulation of the Use of Derivatives and Leverage by Mutual Funds - What Can Regulators Learn from Each Other? - Dominika Paula Gałkiewicz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2014)
This study analyzes current regulation with respect to the use of derivatives and leverage by mutual funds in the U.S. and Germany. After presenting a detailed overview of U.S. and German regulations, this study thoroughly compares the level of flexibility funds have in both countries. I find that funds in the U.S. and Germany face limits on direct leverage (amount of bank borrowing) of up to 33% and 10% of their net assets, respectively. Funds can extend these limits indirectly by using derivatives beyond their net assets (e.g., by selling credit default swaps protection with a notional amount equal to their net assets). Additionally, issuer-oriented rules in the U.S. and Germany account for issuer risk differently: U.S. funds have greater discretion to undervalue derivative exposure compared to German funds. All analyses of this study reveal that under existing derivative and leverage regulation, funds in both countries are able to increase risk by using derivatives up to the point at which it is possible for them to default solely due to investments in derivatives. The results of this study are highly relevant for the public and regulators.
urn:nbn:de:bvb:19-epub-21401-1
Keywords: G15; G18; 330; regulation; mutual funds; leverage; derivative; credit default swaps